Interfacility Transport of Critically Ill Patients. Issue 10 (12th September 2022) - Wilcox, Susan R.; Wax, Randy S.; Meyer, Michael T.; Stocking, Jacqueline C.; Baez, Amado Alejandro; Cohen, Jason; Moss, M. Michele; Frakes, Michael A.; Scruth, Elizabeth A.; Weir, William B.; Zonies, David; Guyette, Francis X.; et al.
Abstract : OBJECTIVES: To assess recent advances in interfacility critical care transport. DATA SOURCES: PubMed English language publications plus chapters and professional organization publications. STUDY SELECTION: Manuscripts including practice manuals and standard (1990–2021) focused on interfacility transport of critically ill patients. DATA EXTRACTION: Review of society guidelines, legislative requirements, objective measures of outcomes, and transport practice standards occurred in work groups assessing definitions and foundations of interfacility transport, transport team composition, and transport specific considerations. Qualitative analysis was performed to characterize current science regarding interfacility transport. DATA SYNTHESIS: The Task Force conducted an integrative review of 496 manuscripts combined with 120 from the authors' collections including nonpeer reviewed publications. After title and abstract screening, 40 underwent full-text review, of which 21 remained for qualitative synthesis. CONCLUSIONS: Since 2004, there have been numerous advances in critical care interfacility transport. Clinical deterioration may be mitigated by appropriate patient selection, pretransport optimization, and transport by a well-resourced team and vehicle. There remains a dearth of high-quality controlled studies, but notable advances in monitoring, en route management, transport modality (air vs ground), as well as team composition and training serve as foundations for future inquiry. Guidance from professional organizations remains uncoupled from enforceable regulations, impeding standardization of transport program quality assessment and verification.